Avaliação da capacitação em programas do INTA: um estudo de caso na área de influência da AER Puerto Rico Misiones - Argentina - Toloza, Roque Rafael (2008)
First of all, training is a process aimed at improving human behaviors which focuses on offering opportunities to people to develop strong thinking and rationality, and to learn in an autonomous, constructive, thoughtful, dialogical, and critical way. Today, the agricultural extension area deploys a series of strategies and methodologies to improve the teaching and learning process. In this context, training initiatives are evaluated based on three programs of INTA, (PH, PFD, ProFeDeR) in the area of influence of AER Puerto Rico, Misiones, Argentina. The objective of this thesis was to evaluate the training initiatives of the different actors involved in each program. In accordance with the characteristics and nature of the research, this study was based on a qualitative and quantitative approach, with the application of a case study methodology. A literature review and a prepared questionnaire for growers and extension professionals were used as research instruments. Based on the grower answers, the results showed that their expectations were satisfied by the training process, and that they really appreciated the technical quality and pertinence of the content. That means that they acknowledge the importance, value, and applicability of the program. The training plays an important role because it helps to improve the transference channels for theoretical and practical knowledge to particular individuals, who recognize and value the acquisition of specific technical competences. The logistic of the courses is highly satisfactory since the date, place, and topics are concrete, and the beneficiaries receive the information in due time and form in order to be able to participate in the event. From the analysis of the enablers, it is possible to conclude that they have limited didactics and pedagogical capacities. On the other hand, the definition of the beneficiaries necessities, the objectives of the course, the contents, the follow-up, and the evaluation were not prepared in cooperation with the beneficiaries, but they were deviced by experts or outlined on the basis of the action program of each project. There was a lack of consideration of the methodological aspects of the learning process. Rarely were indicators considered in the methodology of the training activities to assess the quality and the effect of the course. Futhermore, there was practically no final test carried out at the end of the course. The printed material used during the course is of a very high technical quality, but in several programs this material was not delivered to the participants. However, despite the methodological and, most importantly, pedagogic deficiencies, the training process proved to be efficient in fulfilling what it aimed to achieve.